Corruption in Sub-Saharan Africa - An Impediment to Economic Growth - Ceesay, Lamin (European Scientific Journal, ESJ, 2019)
Sub-Saharan Africa is faced with many challenges. It is a region bulging with resources but cursed with incredible political and economic greed. With a vast ethnic diversity and an often misconstrued cultural lifestyle, which puts the region on the marginalization line. From a historical context, the impact of colonialism has haplessly set the environment for low leadership standards. The background setting for Sub-Saharan Africa’s economic underdevelopment is uninhibited corruption that exists within Sub-Saharan African societies. This institutional corruption takes a triangular cause - cultural, economic and political; each, together with so many other factors threaten Sub-Saharan Africa’s socio-economic development.